Which is Better: E-Book or Printed Book? A Meta-Analysis of Educational Materials in Language Learning - Listanto, Virgiawan; Arlinwibowo, Janu; Permatasari, Anggraeni Dian; Iftitah, Khofifa Najma; Anwas, Ence Oos Mukhamad (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2025)
This study evaluated the effect of electronic books (e-books) on improving language learning outcomes, particularly in core proficiencies such as speaking, writing, and listening, which are identified as key areas of improvement. Using a meta-analysis approach, this research employed a randomized model with experimental and control groups. Data selection followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA) scheme, based on inclusion and exclusion criteria, using the Scopus database. Statistical analyses included tests for heterogeneity, publication bias, total effect size, and moderator variables using analysis of variance. The findings indicate that e-books positively influence the learning process as compared to printed books, with a medium standardized effect size of 0.5. Among languages, Arabic and Turkish benefitted the most from e-book use, while native language learning showed greater improvements than second-language acquisition. Interactive e-books demonstrated significantly higher effectiveness compared to non-interactive ones, though their impact on reading skills was relatively smaller. These results underscore the value of e-books as tools for enhancing language learning. Future efforts should focus on developing interactive e-books tailored to specific languages and proficiency needs to maximize educational potential.